THE INFLUENCE OF HEALTH EDUCATION ABOUT SEX ON ADOLESCENTS' KNOWLEDGE - Monica Christiani Gandey; Djony Ransun; Dorce Sisfiani Sarimin; Yanni Karundeng; Lidya Anita Pantouw (Jurnal Ilmiah Perawat Manado (Juiperdo), 2023)
Background: Sex education that is still considered taboo in Indonesia is one of the causes of adolescents engaging in improper sexual behavior. The purpose of this study was to determine whether there is an effect of sexual health education on adolescent knowledge. This research method uses literature review research, which is research in the form of a literature review of the results of previous research either textbooks or research journals. To obtain data in accordance with the specified topic, researchers conducted a search for national and international journals through three databases, namely Scopus, Science Direct and Google Schoolar. Results with publication years 2010-2020 and researchers obtained 8 journals used for literature review. Conclusion: there is an effect of health education about sex on adolescent knowledge, and the method most often used is the lecture method, with the use of media such as leaflets or power points.